(untitled) (Bangladesh Journal of Botany, 2019)
Effects of gamma rays (0.0, 100, 200 and 300 Gy) and NaCl (0.0, 60 and 120 mM) on the amino acids composition, protein fractions and electrophoretic protein patterns of two Egyptian wheat cultivars (Sids-1 and Sakha-93) were investigated. The results showed that content of amino acids increased by salinity and irradiation doses compared to the control. Concerning, protein fractions of albumin + globulin percentage increased by increasing salinity only and reached the maximum increase by treatment of 120 mM NaCl in the two cultivars. But for glutenin, the highest increase was observed in treatment 100 Gy + 60 mM NaCl. The changes in protein patterns profile were found to be dependent on irradiation dose and salinity level in wheat grains. Total number of protein bands decreased from 20 bands (untreated plants) to 13 bands (irradiated plants) due to treatment of 200 Gy and 60 mM NaCl in Sids-1 cultivar.